2013
DOI: 10.1016/j.atherosclerosis.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant sterol- or stanol-enriched margarine on fasting plasma oxyphytosterol concentrations in healthy subjects

Abstract: Background: Consumption of plant sterols and plant stanols reduces low-density lipoprotein cholesterol (LDL-C) concentrations. At the same time, plasma plant sterol concentrations will increase after plant sterol consumption, but decrease after plant stanol consumption. In contrast to plant stanols, plant sterols can undergo oxidation and form oxyphytosterols. Findings from in vitro and animal studies suggest that oxyphytosterols might be atherogenic. Objective: The objective was to examine whether plant stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 29 publications
2
78
1
Order By: Relevance
“…Nevertheless, oxysitosterol plasma levels are usually higher than campesterols levels, probably due to in vivo oxidation of sterols (67). Considering the higher campesterol oxidation rate compared to sitosterol, as reported in our work, higher potential toxicity of campesterol-enriched foods could be hypothesized.…”
Section: Effect Of the Type Of Sterolmentioning
confidence: 80%
“…Nevertheless, oxysitosterol plasma levels are usually higher than campesterols levels, probably due to in vivo oxidation of sterols (67). Considering the higher campesterol oxidation rate compared to sitosterol, as reported in our work, higher potential toxicity of campesterol-enriched foods could be hypothesized.…”
Section: Effect Of the Type Of Sterolmentioning
confidence: 80%
“…Thus, higher plasma plant sterol concentrations may translate into higher plasma oxyphytosterol concentrations. Intervention trials found conflicting results whether the consumption of a plant sterolenriched margarine for 4 weeks increases plasma 7-ßeOHecampesterol concentrations in healthy individuals [10,12]. Differences with regard to the post-prandial state, the genetic background and different duration of the wash out periods may explain the heterogenicity of the data, however, additional research is needed to address the relation of specific diets with plasma oxyphytosterol concentrations.…”
mentioning
confidence: 86%
“…The incorporation of these exogenously formed oxysterols into the organism through the diet has been widely discussed. Although the intestinal absorption of these compounds (both from cholesterol and plant sterols) has been demonstrated [7][8][9], the relevance of phytosterol absorption versus endogenous formation of these compounds is still under debate, and some scientific evidence has been achieved [10][11]. So, assessment and control of factors affecting sterol oxidation in foodstuffs is a matter of interest for food safety purposes.…”
Section: Introductionmentioning
confidence: 99%